Proposing a Model for Predicting Self-Efficacy Based on Early Maladaptive Schemas Mediated by the Meaning of Life in Remarried Couples - Firouzi , Esmail; Dokaneifard, Farideh; Bostan, Afsaneh (KMAN Counseling & Psychology Nexus, 2025)
The aim of this study was to propose a model for predicting self-efficacy based on early maladaptive schemas, coping strategies, and differentiation, mediated by the meaning of life in remarried couples. This study is classified as basic-applied research in terms of purpose and descriptive-correlational in terms of methodology. The statistical population of the present study included all remarried couples who visited counseling centers in District 3 of Tehran. The sampling method in this study was voluntary and convenience-based. The sample size, based on Cochran’s formula and the nature of the research, and considering potential attrition among participants, was at least 400 individuals, who were selected using the convenience and voluntary sampling method. For data analysis, statistical tests, including multivariate regression and path analysis, were conducted using SPSS software version 24. The results indicated that the proposed model for predicting general self-efficacy based on early maladaptive schemas mediated by the meaning of life in remarried couples fits the empirical data.